The influence of an environmentally relevant polychlorinated biphenyl mixture on the intestinal microbiota in post-weaning mouse dams - Hui Wang; Laura E. Dean; Xueshu Li; Rachel L. Fitzjerrells; Kai Wang; Ashutosh K. Mangalam; Rachel F. Marek; Conner L. Kennedy; Monica M. Ridlon; Audrey Spiegelhoff; Kimberly P. Keil Stietz; Hans-Joachim Lehmler (Environmental Science and Pollution Research, 2026)
Polychlorinated biphenyls (PCBs) are environmental pollutants linked to neurological impairments by mechanisms involving the gut microbiome. This study examines the effects of maternal exposure to a PCB mixture on the gut microbiome of post-weaning mouse dams. Female C57BL/6 J mice were exposed daily to PCBs at different doses (0, 0.1, 1, or 6 mg/kg body weight/day) before mating, and throughout gestation and lactation. Post-weaning intestinal contents from dams were analyzed to assess microbiome abundance and quantify PCBs and their metabolites. PCB exposure affected the composition of microbial taxa, though not significantly. However, topic modeling analysis identified a distinct microbial community that was significantly more prevalent in the control group compared to post-weaning mouse dams exposed to the MARBLES mixture at medium and high doses. Complex PCBs and metabolite mixtures were detected in the intestinal contents. Certain PCBs and their metabolites were associated with changes in bacterial abundance, as determined by network analysis. These findings show that individual PCBs and their metabolites can affect gut microbial communities, potentially contributing to neurological impairments in mice exposed to PCBs during gestation and lactation. Graphical Abstract

Identification of polychlorinated biphenyls (PCBs) and PCB metabolites associated with changes in the gut microbiome of female mice exposed to an environmental PCB mixture - Laura E. Dean; Hui Wang; Xueshu Li; Rachel L. Fitzjerrells; Anthony E. Valenzuela; Kari Neier; Janine M. LaSalle; Ashutosh Mangalam; Pamela J. Lein; Hans-Joachim Lehmler (Journal of Hazardous Materials, 2025)